PENGARUH LEVERAGE, UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2023 - Jenny Zain; Agnes sihombing; Reny Vatrecia Lumbantoruan; Malvin Orlando Chandra; Oky Syahputra (JURNAL LENTERA BISNIS, 2025)
This research was carried out to test the effect of Leverage (X1), Company Size (X2), Company Growth (X3) and Profitability (X4) on Company Value (Y). This research used secondary data, namely the company's financial statements. The object of analysis is Property and Real Estate companies listed on the Indonesia Stock Exchange during the 2020-2023 period. The sampling technique used in this research was purposive sampling which resulted in 23 companies with a total observation of 92 samples. Data were analyzed using a multiple linear regression analysis model, coefficient of determination, F Test, t Test. The results of the simultaneous hypothesis show that Leverage, Company Size, Company Growth, and Profitability have an effect on Company Value. The results of the partial hypothesis study show that the variables Leverage, Company Size, Company Growth do not have a significant effect on Company Value while Profitability has a negative and significant effect on Company Value. The results of the determination coefficient analysis obtained an adjusted R square of 0.287, meaning that the variation in the Company Value variable that can be explained by Leverage, Company Size, Company Growth, and Profitability is 28.7%, while the remaining 72.3% is influenced by other variables outside the regression model in this study.